KADAR SERUM KREATININ DAN KALIUM PASIEN DENGAN DAN TANPA DIABETES JENIS (TIPE) II - Tonang Dwi Ardyanto; Tahono Tahono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Hyperkalemia is a metabolic disorder caused by either renal insufficiency for potassium excretion (like in renal failure), thedysmechanism of potassium transportation into the intracellular space (regards on the hyperglycemia status) or combinations of thoseetiologies. In nephropathy diabetic patients, hyporeninemic hypoaldosteronism syndrome might also be the etiology resulting from thehigh potassium level. The objective of the present study was to evaluate the correlation between the serum creatinine and potassiumlevel in patient with and without type II diabetes. The data of this study were drawn from patients admitted to the laboratory for themeasurement of serum creatinine and potassium with or without the measurement of blood glucose level at the Clinical PathologyLaboratory of Moewardi Hospital in Surakarta. The subjects were then classified into two groups: A (non-diabetic patients) and B(diabetic patients). The data were analyzed statistically with T-student test and Pearson Correlation test based on the total samples, pereach group (A and B groups) and the diabetic status (only B group) one. In this study so far it was found that the serum creatinine andpotassium level were significantly correlated in the total sample and group A analysis (p<0.05). Surprisingly, the correlation was notfound or very weak in group B (p>0.05). Furthermore, no correlation was found in the analysis based on the diabetic status amongthe B group subjects (p>0.05). It can be suggested that other factors may play a significant influence on the correlation between thehyperglycemia state, renal failure and serum potassium level in diabetic patients. Further detailed analysis should be warranted toelucidate those factors.